Analytical study on heat transfer addition of different nano liquids in vertical rotating system with CFD - G. Mahadevi; Bala Siddulu Malga; B.R. Sreedhar; G. Deepa (Utilitas Mathematica, 2025)
This study presents an analytical investigation into the heat transfer performance of various nanofluids—namely copper oxide (CuO), aluminum oxide (Al₂O₃), and zinc oxide (ZnO) dispersed in water—within a vertical rotating system. The relationship between the system's thermal and flow properties and the type of nanoparticle, volume percent, and rotating speed is investigated in the analysis. The boundary layer theory and similarity transformations are used to convert the governing partial differential equations into a set of nonlinear ordinary differential equations. Then, the equations are solved numerically. The results demonstrate that compared to the base fluid, heat transmission is significantly enhanced with the inclusion of nanoparticles. The thermal conductivity is highest in nanofluids comprising CuO and water, then in nanofluids containing Al₂O₃ and ZnO. Also, the thermal boundary layer and flow velocity are both significantly affected by the rotational motion. Thermal management of rotating machinery and industrial processes can benefit from the study's emphasis on nanofluids' ability to optimize heat exchange in rotating systems.